2017
DOI: 10.1103/physrevfluids.2.083302
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing elastic turbulence in channel flows at low Reynolds number

Abstract: We experimentally investigate the flow of a viscoelastic fluid in a parallel shear geometry at low Reynolds number. As the flow becomes unstable via a nonlinear subcritical instability, velocimetry measurements show non-periodic fluctuations over a broad range of frequencies and wavelengths, consistent with the main features of elastic turbulence. Using the same experimental setup, we compare these features to those in the flow around cylinders, which is upstream to the parallel shear region; we find significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
103
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 83 publications
(122 citation statements)
references
References 42 publications
18
103
1
Order By: Relevance
“…Once sufficiently perturbed, the flow remains unsteady far downstream of the perturbation; this observation suggests the generation of a new dynamical flow state in which fluctuations are sustained indefinitely . However, the statistics of the flow fluctuations are markedly different near the pillars and far downstream . As the flow progresses downstream, regions of positive or negative streamwise velocity fluctuations coalesce, leading to large rolling advection cell structures (Figure b–d).…”
Section: Unstable Flow Of Polymer Solutionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Once sufficiently perturbed, the flow remains unsteady far downstream of the perturbation; this observation suggests the generation of a new dynamical flow state in which fluctuations are sustained indefinitely . However, the statistics of the flow fluctuations are markedly different near the pillars and far downstream . As the flow progresses downstream, regions of positive or negative streamwise velocity fluctuations coalesce, leading to large rolling advection cell structures (Figure b–d).…”
Section: Unstable Flow Of Polymer Solutionsmentioning
confidence: 98%
“…b) Schematic of microfluidic porous media, and kymographs of streamwise velocity fluctuations ( u ′) c) nearby and d)far downstream of circular pillar array. Reproduced with permission . Copyright 2017, American Physical Society.…”
Section: Unstable Flow Of Polymer Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large amplitude perturbations to the base flow were introduced by an array of cylinders mounted vertically near the entrance to the channel. It was observed that the flow became unstable for a sufficiently high Weissenberg number (defined in References and as Wi=λγ˙, where λ is the fluid relaxation time and γ˙ is the mean flow strain rate), Wi ≥ 5.2, and for a sufficiently energetic flow disturbance (15 cylinders). In fact, the instability was observed far downstream (200 channel widths) from the channel entrance, where the flow transitioned to a chaotic, turbulent‐like state.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the elongational strain rates were apparently amplified downstream of the cylinders, indicating the possibility of significant stretching of the polymer molecules. Experimental evidence thus far suggests that the observed chaotic flow is due to a nonlinear subcritical instability …”
Section: Introductionmentioning
confidence: 99%